Commutation Performance Enhancement of Sensorless BLDC Motor Using Finite Impulse Response Filtering in Back-EMF Detection - Ony Asrarul Qudsi; Era Purwanto; Sulis Wanto; Muhammad Rizani Rusli (Jurnal Teknologi Terpadu, 2026)
Sensorless Brushless Direct Current (BLDC) motors are widely used in industrial applications due to their high efficiency and low maintenance requirements. However, commutation based on Back-Electromotive Force (Back-EMF) zero-crossing detection is highly susceptible to noise, leading to commutation timing inaccuracies. This paper proposes an improvement in sensorless BLDC motor commutation performance through the application of a Finite Impulse Response (FIR) digital filter to the Back-EMF detection signal. The FIR filter is designed to attenuate high-frequency harmonic components without compromising system stability. The proposed method is implemented on a three-phase inverter system employing six-step commutation controlled by a microcontroller. Simulation results indicate that the dominant noise frequency in the Back-EMF signal is reduced from 347.6 Hz to 212.5 Hz after filtering. Furthermore, hardware experimental results demonstrate a reduction in disturbance frequency from 317.23 Hz to 265.43 Hz. The application of the FIR filter improves the reliability of zero-crossing detection and enhances commutation timing accuracy compared to an unfiltered system. These results confirm that the proposed approach is effective in improving the commutation performance of sensorless BLDC motors based on Back-EMF detection.